Sialendoscopy increases saliva secretion and reduces xerostomia up to 60 weeks in Sjögren's syndrome patients: a randomized controlled study. (19th September 2020) - Karagozoglu, K Hakki; Vissink, Arjan; Forouzanfar, Tim; de Visscher, Jan G A M; Maarse, Floor; Brand, Henk S; van de Ven, Peter M; Jager, Derk H Jan
Abstract: Objective: To assess the effect of sialendoscopy of the major salivary glands on salivary flow and xerostomia in patients with Sjögren's syndrome (SS). Methods: Forty-five patients with SS were randomly assigned to a control group (no irrigation, control, n = 15), to irrigation of the major salivary glands with saline (saline, n = 15) or to irrigation with saline followed by corticosteroid application (triamcinolone acetonide in saline, saline/TA, n = 15). Unstimulated whole saliva flow (UWSF), chewing-stimulated whole saliva flow (SWSF), citric acid-stimulated parotid flow, Clinical Oral Dryness Score (CODS), Xerostomia Inventory (XI) and EULAR SS Patient Reported Index (ESSPRI) scores were obtained 1 week before (T0), and 1, 8, 16, 24, 36, 48 and 60 weeks after sialendoscopy. Data were analysed using linear mixed models. Results: Irrespective of the irrigation protocol used, sialendoscopy resulted in an increased salivary flow during follow-up up to 60 weeks. Significant between-group differences in the longitudinal course of outcomes were found for UWSF, SWSF, XI and ESSPRI scores ( P = 0.028, P = 0.001, P = 0.03, P = 0.021, respectively). UWSF at 60 weeks was higher compared with T0 in the saline group (median: 0.14 vs median: 0.10, P = 0.02) and in the saline/TA group (median: 0.20, vs 0.13, P = 0.035). In the saline/TA group SWSF at 48 weeks was higher compared with T0 (median: 0.74 vs 0.38, P = 0.004). Increase in unstimulated salivary flow was also reflected in improved CODS, XI and ESSPRI scores compared with baseline. Conclusion: Irrigation of the major salivary glands in patients with SS increases salivary flow and reduces xerostomia.